A Mobile Management System for Reforming Subsidies Distribution In Egypt. Issue 1 (5th December 2017) - El‐Shishtawy, Tarek
Abstract: This paper aims to show how advances in mobile technologies can help solve social and political aspects involved in the reform of subsidies in developing countries. It describes the work done to build a mobile‐based supportive network that integrates all subsidy partners: governmental, non‐governmental organizations, merchants, and beneficiaries. One main contribution of this work is the setting of a framework for identifying the requirements of information systems for subsidies distribution. Seven domains were identified to build a Mobile Subsidizing Business Model (MSBM). Based on MSBM, detailed requirements were gathered in three stages, each having its appropriate methodology. We focus on the layered architecture implementation of the mobile subsidizing system to break down complexities due to variations in mobile technologies, different business rules, and multiple distribution scenarios.